2011
DOI: 10.5507/bp.2011.009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Patients With Peripheral T-Cell Lymphoma Treated With First-Line Intensive Chemotherapy Followed by Autologous Stem Cell Transplantation

Abstract: Background. Peripheral T-cell lymphomas (PTCL) are infrequent subtypes of non-Hodgkin's lymphomas. The clinical course is aggressive and the median survival is about 2-3 years. An optimal first-line chemotherapy protocol has not been established and the role of high-dose therapy with autologous stem cell transplantation (ASCT) is still unclear.Aim. To analyze the long-term outcome of unselected PTCL patients treated with intensive first-line chemotherapy with high-dose therapy and ASCT.Method. Here we report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…A number of retrospective [11][12][13][14][15][16][17][18]29] and prospective [8][9][10]22,30,31] studies have reported an apparent outcome advantage from the use of upfront HDT/ASCT in PTCL patients with chemosensitive disease. In the present study, less than half of PTCL patients were considered eligible for inclusion in CTs with multiagent chemotherapy followed by SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of retrospective [11][12][13][14][15][16][17][18]29] and prospective [8][9][10]22,30,31] studies have reported an apparent outcome advantage from the use of upfront HDT/ASCT in PTCL patients with chemosensitive disease. In the present study, less than half of PTCL patients were considered eligible for inclusion in CTs with multiagent chemotherapy followed by SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, large phase II trials testing upfront high-dose chemotherapy (HDT) and autologous SCT (ASCT) have shown good feasibility and a possible beneficial effect on clinical outcome [8][9][10]. With the obvious caveat of patient selection, retrospective studies also seem to support this impression, particularly in patients exhibiting chemosensitive disease [11][12][13][14][15][16][17][18]. National guidelines, such as those from the National Comprehensive Cancer Network, include HDT/ASCT as a recommended option for consolidation after first remission in patients with histologies other than anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALCL) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Among the patients treated with HDT/ASCT, analysis of OS in terms of the International Prognostic Index (IPI) at diagnosis was reported in 9 studies [23,25,28,30,36,37,38,39,45]. Six studies, including 347 patients, were enrolled in this meta-analysis [23,28,36,38,39,45].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies, including 347 patients, were enrolled in this meta-analysis [23,28,36,38,39,45]. The summary-estimated HR for OS was 0.36 (95% CI 0.22-0.60, I 2 49%), as determined with the fixed-effect model, suggesting a significant survival advantage after transplantation for patients with low IPI risk compared to patients with high IPI risk (p < 0.0001; fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation